Black Medic (Medicago lupulina) Germination Response to Temperature and Osmotic Potential, and a Novel Growing Degree-Day Accounting Restriction for Heat-Limited Germination. Issue 2 (18th December 2018) - Sharpe, Shaun M.; Boyd, Nathan S.
Abstract: Black medic ( Medicago lupulina L.) is a problem weed species in Florida strawberry [ Fragaria × ananassa (Weston) Duchesne ex Rozier (pro sp.) [ chiloensis × virginiana ]] production. It competes with the crop and hinders harvest efficiency. A reductionist approach is being undertaken to predict M. lupulina field emergence to coordinate control tactics. Germination is the first model component to be developed. The objectives were to study the effect of osmotic potential and temperature on seed germination and to develop the germination component for reductionist emergence modeling. Trials were initiated using petri dishes in incubators to test M. lupulina germination in response to osmotic potential (0 to −1 MPa) and constant (5 to 40 C) and fluctuating temperatures (35/25, 35/20, 25/15, and 25/10 C, 12/12-h duration). Medicago lupulina germinated between 5 and 35 C. Optimal germination was between 10 and 20 C. Germination was negatively impacted by temperatures above the optimum. Fluctuating temperatures did not influence germination compared with constant temperatures. A reduction in osmotic potential from 0 to −0.25 MPa reduced germination from 43% to 14%. Three temperature-mediated germination trends were identified: standard increases and plateau up to 20 C, reduced germination between 20 and 35 C, and no germination at 40 C. A novel restriction to daily growing degree-day (GDD) accounting was developed for heat-limited germination. The germination restriction accounted for the optimum and maximum temperature, diminishing returns of exposure to higher temperatures, and the negative impact of higher temperatures above the optimum range. Determination logic and the new daily GDD accounting formula aligned GDD accumulation across all temperatures to be described by a Weibull formula (R 2 = 0.5199). Results establish the germination component for reductionist emergence modeling, but further study is required to account for dormancy and PRE growth.